Individual differences in values determine the relative persuasiveness of biospheric, economic and combined appeals - Van den Broek, Karlijn; Bolderdijk, Jan Willem; Steg, Linda (Journal of environmental psychology, 2017)
Many environmental campaigns highlight both the environmental and financial benefits of behaviour change, in the hope of motivating a broad audience. But are such mixed appeals more persuasive than separate appeals? We argue that messages tailored to match recipient's prioritised values are more persuasive than combined appeals. We conducted a questionnaire study to assess the persuasiveness of economic, environmental, and mixed appeals (N = 210). As expected, individual differences in values moderated the persuasive power of the different appeals. Importantly, we found that appeals that matched the recipients' values were more persuasive than the combined appeal. Interestingly, personal norms also acted as a moderator. These findings suggest that environmental campaigns aimed to induce behavioural change can benefit from tailoring persuasive messages to idiosyncratic characteristics of their target group, rather than employing a one-size-fits-all message.
Gesehen am 06.07.2018
Available online 28 July 2017